Evaluación del transplante y prendimiento de tres especies forestales nativas en la zona de Saposoa, región San-Martín - Jimeno García, Teodorico (1999)
The present experiment was carried out in the sector Montevideo, jurisdiction of the District of Saposoa, County of the Huallaga-Region San Martin, of October 97 30 at January 98 30. Geographically with 7° 10' South Latitude, 77° 15 ' Longitud Oeste and 307 m.s.am in a texture floor Sandy Franco; with pH 7.1, CaMg 22.3 meq/100, M.O 3.0%, F 10.0 ppm and K20 0.38 meq/100. The place is characterized to have a tropical dry forest (bs -T), with precipitation annual average of 1,120 mm and temperature I average yearly of 24.5° C. For the statistical analysis the statistical design was used “Complete Block Randomizado” (BCR) with factorial arrangement of 3 x 2. The treatments in study were: Cedar with earth Bread (E1T1), Paliperro with earth Bread (E2T1), Capirona with earth Bread (E3T1), and Cedar to naked root (E1T2), Paliperro to naked root (E2 T2), Capirona to naked root (E3T2) whose results in height of growth were: (E1T1) 59.07 cm, (E2T1) 50.06 cm, (E3T1) 44.03 cm, (E1T2) 53.58 cm, (E2T2) 56.52 cm, (E3T2) 37.64 cm., subjected to the variance analysis and the test of Duncan. As for the increment of growth of the species studied by evaluations and transplant modalities you can indicate: Capirona (Calycophyllum spruceanum Bent) 7.2 cm, Paliperro (Vítex sp Bert) 4.3 cm, Cedar (Cedrela odorata L.) 4.0 cm. The cost of establishment of the plantation ascends to the mmi of 381.12 new suns for the transplant modality to earth bread and 224.71 new soles/ha for file transplant modality to naked root